Alternative Splicing of the Lobster (Homarus americanus) Crustacean Hyperglycemic Hormone A and B Genes Produce 2 Protein Variants Involved in Vitellogenin Inhibition - Wang, Cheng Gui; Wang, Wei; Shi, Li Li; Shen, Yu Chun; Chan, Siuming F. (Frontiers in Marine Science, 2022)
Current BLASTP search analysis results suggested that the lobster (Homarus americanus) HaCHH-A and HaCHH-B may be derived from two different four-exon genes. Repeated tissue expression studies have revealed much different expression patterns of these two genes from those reported in the past. With RT-PCR, rapid amplification of complementary DNA (cDNA) ends (RACE), and genomic DNA cloning, we confirmed that the HaCHH-A and HaCHH-B transcripts were derived from two different four-exon CHH genes. By an alternative splicing mechanism, each gene can produce different but larger transcript variants (i.e., sHaCHH-A and sHaCHH-B) mainly in different non-eyestalk tissues of the females. The larger and unspliced transcripts can be detected in the hepatopancreas, gill, heart, nerve cord, brain, ovary, and thoracic ganglion of the reproductive females. The expression patterns of sHaCHH-A and sHaCHH-B in other non-eyestalk tissues suggest that these transcripts have a wide spectrum of expressions during the female reproductive cycle. An in vitro organ explant culture system was developed to investigate the reproductive function of these cDNAs. The results showed that the recombinant proteins for sHaCHH-A and sHaCHH-B inhibited the gene expression of vitellogenin, whereas the double-stranded RNA (dsRNA) for sHaCHH-A and sHaCHH-B stimulated the expression of the vitellogenin gene in vitro. The results of the study may provide insights for the development of techniques to induce gonad development without using eyestalk ablation operation. This is the first in-depth report of the characterization of two four-exon CHH genes in a crustacean.